The Near‐Surface Boundary Layer of Hurricane Laura (2020) at Landfall - Karen Ann Kosiba; Joshua Wurman; Paul Robinson (Geophysical Research Letters)
Abstract While challenging, quantification of the near‐surface landfalling hurricane wind field is necessary for understanding hurricane intensity changes and damage potential. Using single‐ and dual‐Doppler Doppler on Wheels and in situ anemometer data, the wind structure of the very near‐surface boundary layer of Hurricane Laura (2020) is characterized. Small‐scale hurricane boundary layer (HBL) rolls (HBLRs) with a median size of approximately 400 m are present throughout much of the landfall, but are most vigorous in the eyewall. The maximum turbulent kinetic energy (TKE) and momentum flux associated with HBLRs occur in the eyewall and are much larger than previously documented at landfall. DOW‐derived and anemometer‐derived TKE values are comparable. Observed maximum surface gusts were consistent with the maximum radar wind speeds aloft, suggesting the importance of vertical transport within the HBL by sub‐kilometer scale structures for the enhancement of surface wind speeds.